«Duro se nos hizo de creer la continencia del mozo»: Armonía homosocial y escándalo. Las aporías de la heteronormatividad en el episodio de Eugenio, Leandra y Vicente de la Roca (Quijote, 1, 51) - Juan Diego Vila (E-Spania)
The pastoral sequence on the eventual ill-fated fate of Leandra (I, 51) puts on stage the scandal of those beliefs that govern, unconsciously, the illusionism of the sex-gender division of the villages. All the aforementioned characters, and even the most seasoned critics, discuss about the fugitive’s indirimitable virginal status; nobody, on the contrary, notices to what extent the homosocial harmony of the pleasant meadow forged a posteriori by the affronted suitors conceals, in truth, a mystery more abject than the young woman’s ill-fated hymen: the possibility that, against the dominant, Vicente de la Rosa/Roca does not feel regulated by heteronormativity.For Vicente -in our opinion- is not the figure of the male continent with which the anguish of the suitors is soothed, but rather the image in flight and sacrilegious of the man who does not desire the maiden and reveals himself to the social and unconscious command to deflower her.